Neuropeptides and Neurotransmitters That Modulate Thalamo‐Cortical Pathways Relevant to Migraine Headache. (9th May 2017) - Noseda, Rodrigo; Borsook, David; Burstein, Rami
Abstract : Dynamic thalamic regulation of sensory signals allows the cortex to adjust better to rapidly changing behavioral, physiological, and environmental demands. To fulfill this role, thalamic neurons must themselves be subjected to constantly changing modulatory inputs that originate in multiple neurochemical pathways involved in autonomic, affective, and cognitive functions. This review defines a chemical framework for thinking about the complexity of factors that modulate the response properties of relay trigeminovascular thalamic neurons. Following the presentation of scientific evidence for monosynaptic connections between thalamic trigeminovascular neurons and axons containing glutamate, GABA, dopamine, noradrenaline, serotonin, histamine, orexin, and melanin‐concentrating hormone, this review synthesizes a large body of data to propose that the transmission of headache‐related nociceptive signals from the thalamus to the cortex is modulated by potentially opposing forces and that the so‐called 'decision' of which system (neuropeptide/neurotransmitter) will dominate the firing of a trigeminovascular thalamic neuron at any given time is determined by the constantly changing physiological (sleep, wakefulness, food intake, body temperature, heart rate, blood pressure), behavioral (addiction, isolation), cognitive (attention, learning, memory use), and affective (stress, anxiety, depression, anger) adjustment needed to keep homeostasis.